History and Future of School Safety Research. Issue 2 (3rd December 2020) - Cornell, Dewey G.; Mayer, Matthew J.; Sulkowski, Michael L.
Abstract: This article summarizes the accomplishments of research on school safety in the past quarter century, identifies important gaps, and indicates promising directions for further progress. Although closely related, there are distinguishable bodies of research on physical and psychological safety. Physical safety research concerns the prevention of violent attacks through security measures, school discipline, and threat assessment. Psychological safety is focused on protecting students from less severe, but serious, acts of peer aggression such as harassment and bullying, and includes research on multitiered programs and school climate. This article recognizes substantial support for some school safety practices while emphasizing the need for research on other widely used practices. School safety research has much to offer school psychologists in fostering physically and psychologically safe schools that produce students who develop into well-educated and responsible citizens. Impact Statement This article reviews a quarter century of research on school safety in order to identify both successful and unsuccessful strategies for keeping schools physically and psychological safe for students. School security measures and a zero tolerance approach to discipline have yielded little evidence of effectiveness and can have negative consequences for students. More promising alternatives that emphasize prevention include school threat assessment, multitiered programs concerned with positive behavioral interventions and social–emotional learning, and maintenance of a supportive and structured school climate.